Treatment of Wastewaters from Livestock Farms - Erika Beilicci; Robert Beilicci; Camelia Stefanescu (Scientific Papers Animal Science and Biotechnologies, 2023)
Raw wastewater from livestock farms is a mixture of faeces, urine, bedding materials, and water from washing and cannot be distributed on agricultural land in this state, and not discharged in natural emissions. That is why it is necessary to purify them, in order to retain and neutralize the harmful substances present in these wastewaters from animal farms, which are not accepted in the aquatic environment where the treated water is discharged and which allow the physical-chemical properties of the water to be restored before use.